ANALYSIS THE INFLUENCE OF WORK-FAMILY SUPPORTIVE SUPERVISOR TO JOB INVOLVEMENT AND JOB SATISFACTION WITH CAREER COMPETENCIES AS AN INTERVENING VARIABLE (Case Study of Nurse at PGI Cikini Hospital Jakarta) - Johnpray, Paguh Raja; Suharnomo, Suharnomo (Diponegoro Journal of Management, 2015)
Intense competition is increasing nowadays among companies globally. Competition which made the employees to increase their capabilities and competencies, is confiscate their time and the need of balance between work and family. Hospital as a place where a person need of care and protection are now beginning to compete closely in the selection of employees, services provided, and the development of its employees. Nurse is an employee who must give a full attention to each condition and time, also require attention in its work. As nurse provides care to patients, he or she also require attention such as policy and regulatory support for any problems that occur both in work and family.This study was conducted to explore the relationship between work-family supportive supervisor, career competencies, job involvement, and job satisfaction. Data were collected from a sample of 162 respondents who worked as a nurse at PGI Cikini Hospital in Jakarta. This study used Structural Equation Modeling (SEM) to examine and estimate the relationship between the constructs. The results of this study indicate that work-family supportive supervisor has a positive and significant impact on the career competencies. Career competencies has a positive and significant impact on job involvement. Career competencies has a positive and significant impact on job satisfaction. Work-family supportive supervisor has a positive and significant impact on job involvement. Work-family supportive supervisor has a positive and significant impact on job satisfaction.A total of 162 respondents with a percentage of 96.30% women showed that women need the support and policies conducive to achieving a balance between work and family. Finally, this study highlights the importance of work-family supportive supervisor and career competencies in improving job involvement and job satisfaction. This study provides insights into how the human resources department can retain qualified staff and improving employee satisfaction.